Biotransformation of (-)-Epigallocatechin-3-O-gallate into (-)-2R,3S-Dihydromyricetin by the Endophytic Fungus Diaporthe sp. E Isolate Obtained from a Tea Plant - ANDRIA AGUSTA (HAYATI Journal of Biosciences, 2007)
Endophytic fungi have been reported possess an interesting ability to mimic their host plant metabolites. Several fungi also show their specific capability to biotransform the chemical constituents of the host plant. The endophytic fungus Diaporthe sp. E isolate obtained from young stem of a tea plant (Camellia sinensis) show their unique capability to biotransform (-)-epigallocatechin-3-O-gallate [(-)-EGCG] into a major product in glucose-peptone-yeast extract medium that incubated under dark condition at 27 oC for 48 h. The major biotransformation product were isolated and purified through column chromatography techniques using Sephadex LH-20 and silica gel. The chemical structure of the major product were elucidated as (-)-2R,3S-dihydromyricetin based on their IR, FAB-MS, 1D- and 2D-NMR spectra. Key words: (-)-2R,3S-dihydromyricetin, (-)-EGCG, (-)-2R,3R,4R-leucodelphynidin, biotransformation, Diaporthe sp. E isolate, endophytic fungus, Camellia sinensis